1976
DOI: 10.1210/endo-98-1-139
|View full text |Cite
|
Sign up to set email alerts
|

Serum Growth Hormone and Prolactin During and After the Development of the Obese-Hyperglycemic Syndrome in Mice

Abstract: Mice with the recessively inherited obese-hyperglycemic syndrome (ob/ob) and their nonobese litter mates were studied over a 26-week period. The body weights and serum glucose levels of ob/ob mice began to rise markedly at 5-6 weeks of age and remained elevated throughout the period of study. Obese mice were significantly heavier (P less than .001) and had higher serum glucose levels (P less than .001) than lean mice, but obese mice had variably lower serum growth hormone (GH) and prolactin (PRL) levels (P les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 0 publications
3
19
1
Order By: Relevance
“…On the other hand, our results are not in keeping with those reported by Larson et al [1976] in male mice and by Seggie and Brown [1976] and Taya and lgarashi [ 1974] in male rats. Circadian rhythms in the secre tion of PRL were not found in all these investigations.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, our results are not in keeping with those reported by Larson et al [1976] in male mice and by Seggie and Brown [1976] and Taya and lgarashi [ 1974] in male rats. Circadian rhythms in the secre tion of PRL were not found in all these investigations.…”
Section: Discussioncontrasting
confidence: 99%
“…Because body mass index and several metabolic substrates have an effect on GH secretion [13], a relationship between leptin and GH has been investigated in several species including man. The genetically ob/ob mouse has reduced plasma GH levels [14]. In humans, Clement et al [15]recently found that a mutation of the leptin receptor gene caused obesity and a reduction in GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroxine levels are depressed in 6-20-day-old ob/ob mice [31], although they are normal after weaning [32]. Circulating growth hormone is reported to be normal [33] or decreased [34] in obese mice, but may not contribute to the decrease in skeletal musculature since plasma somatomedin concentration is normal [35]. It could be argued also that the marked hypoactivity of obese mice may trigger a reduction in size of their presumably less frequently used fast twitch skeletal muscle fibres.…”
Section: Discussionmentioning
confidence: 99%